EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE TO JOB SATISFACTION AT PT MUSIM MAS, MEDAN - Lila Maria Kaban; Vella Faizal (Journal of Accounting and Management Innovation, 2021)
There are more and more multinational enterprises growing in Indonesia that makes foreign employees are increasing every year. Thus, it is important for local workers to understand the leadership style of expatriates from the companies’ leaders and managers. The purpose of this research is to see the effect of transformational leadership style on job satisfaction conducted at PT Musim Mas, Medan. This research uses quantitative method with simple random sampling of 36 employees working in the company. The test results show that transformational leadership style has a positive significant effect on job satisfaction at PT Musim Mas, Medan as much as 69.5%. Keywords: Transformational Leadership; Job Satisfaction; International Business